2020
DOI: 10.3390/md18120635
|View full text |Cite
|
Sign up to set email alerts
|

Herring Milt and Herring Milt Protein Hydrolysate Are Equally Effective in Improving Insulin Sensitivity and Pancreatic Beta-Cell Function in Diet-Induced Obese- and Insulin-Resistant Mice

Abstract: Although genetic predisposition influences the onset and progression of insulin resistance and diabetes, dietary nutrients are critical. In general, protein is beneficial relative to carbohydrate and fat but dependent on protein source. Our recent study demonstrated that 70% replacement of dietary casein protein with the equivalent quantity of protein derived from herring milt protein hydrolysate (HMPH; herring milt with proteins being enzymatically hydrolyzed) significantly improved insulin resistance and glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 102 publications
(152 reference statements)
0
21
0
Order By: Relevance
“…Consumers are increasingly aware of the impact of specific nutrients on health and disease and this trend has, in turn, been driving food market growth, in particular the sector of functional foods, dietary supplements, and nutraceuticals. It is emerging that consumption of fat and carbohydrates is associated with the onset and progression of metabolic diseases, while protein intake, generally, is not [ 13 , 14 , 15 ]. Consistently, the global market for protein ingredients was USD 38.5 billion in 2020 and is anticipated to experience a compound annual growth rate (CAGR) of 10.5% from 2021 to 2028 ( (accessed on 28 November 2021)).…”
Section: Introductionmentioning
confidence: 99%
“…Consumers are increasingly aware of the impact of specific nutrients on health and disease and this trend has, in turn, been driving food market growth, in particular the sector of functional foods, dietary supplements, and nutraceuticals. It is emerging that consumption of fat and carbohydrates is associated with the onset and progression of metabolic diseases, while protein intake, generally, is not [ 13 , 14 , 15 ]. Consistently, the global market for protein ingredients was USD 38.5 billion in 2020 and is anticipated to experience a compound annual growth rate (CAGR) of 10.5% from 2021 to 2028 ( (accessed on 28 November 2021)).…”
Section: Introductionmentioning
confidence: 99%
“…The previous study did not show such results for HMH2, which would be explained by the lower doses given to the mice [ 17 ]. Interestingly, a recent study showed that replacing 70% dietary casein protein with herring milt hydrolysate (dose not specified) in comparison to a high-fat diet reduced in vivo obesity, fasting glycemia, and fasting serum insulin, and improved glucose tolerance [ 28 ]. The HMH supplements in the present study did not show such positive results.…”
Section: Resultsmentioning
confidence: 99%
“…Blood samples were collected from tail veins of normal and experimental ob / ob mice at 0, 30, 60, 90, 120, and 180 min. Changes in blood glucose levels in different groups were confirmed using a glucose meter (Accu-Chek Performance Kit, Roche Diagnostics Korea Co., Ltd., Seoul, Korea) [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…The result was normalized against the β-actin mRNA signal. The primer sequences used in this study are listed in Table 4 [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation